10.1111/acn.v9999.9999 (CrossRef Listing of Deleted DOIs, 2000)
Introduction Despite the free childhood dental care in New Zealand (NZ), the need for extensive dental treatment, particularly hospital dental treatment is on the rise. This study aimed to explore the perspectives of oral health professionals and cariology experts on the use of silver diamine fluoride (SDF) in reducing outpatient dental hospitalisation and oral health inequity among NZ paediatric patients. Methods A qualitative approach was applied. Thirteen registered oral health professionals, who routinely provide restorative and curative care to children in NZ, alongside cariology experts, participated in semi-structured one-to-one interviews. The transcripts were analysed using an inductive thematic approach. Results The data analysis led to three major themes: Theme one: 'Black Diamond', referring to SDF's benefits and effectiveness in caries management with significant focus on its potential to reduce the demand for dental treatment under general anaesthesia (GA). However, post-treatment black staining raised universal concern. Theme two: Transparency, emphasising public awareness, dental professionals' knowledge and informed consent. Thus, informed consent must be discussed with patients and caregivers who must understand SDF outcomes. Theme three: Teeth tell stories, highlighting oral health inequity. While SDF may be a game changer for caries management and enhancing oral health care accessibility, addressing systemic inequity is essential to improve oral health equity. Conclusion SDF is a valuable, yet limited option for arresting caries and reducing GA treatment demand. Clear communication and informed consent are important before SDF application. While it may enhance dental care accessibility, SDF alone is not sufficient to eliminate oral health inequities.